HUBUNGAN DUKUNGAN KELUARGA TERHADAP PRAKTEK PEMBERIAN ASI DI WILAYAH PUSKESMAS SUDIANG RAYA KOTA MAKASSAR - Lydia fanny; Retno Sri Lestari; Chaerunnimah Chaerunnimah (Media Gizi Pangan, 2017)
Backgrounds: Exclusive breastfeeding is beneficial to reduce child mortality and improve maternal health that compatible with the one of Sustainable Development Goals (SDGs) that ensuring the child get exclusive breastfeeding during the first six months of the birth.Objectives: This research aims to determine the relationship of family support to the practice of giving breastmilk to the baby in PuskesmasSudiang Raya Makassar area.Methods: This research is an analytic survey with Cross Sectional design. The population was 126 breastfeeding mothers. The statistical analysis used is the Coefficient of Contingency with α = 0,05.Results: The result showed that mothers who give breastmilk to their babies have a good family support of 57,6% and there is a relationship between family support and the practice of giving breastmilk to the baby in PuskesmasSudiang Raya Makassar area.Conclusions: Good family support can increase the amount of mothers who give breastmilk to their baby.Keywords: Breastmilk, Family Support, Baby, Mother